Libraries architecture and design as a subject of teaching at the library-information faculty - M. N. Kolesnikova; Ye. V. Bakhtina; V. P. Timonin (Библиосфера)
The article represents major issues of academic subject «Libraries architecture and design» at the library-information faculty of Saint-Petersburg State Institute of Culture. Authors examine the course evolution, present its scientific and educational base (dissertations, monographs, textbooks, etc.). Goals and objectives of the discipline are identified. The represented structure of the discipline contains the following sections: 1. Introduction to architecture. Theoretical bases of architectural design; 2. Architecture and planning of library buildings. 3. Functional division of libraries’ rooms; 4. Library interiors; 5. Design of library iconic-information systems. Students are familiarized with basic terminology and theoretical approaches of architectural design in the training process. Architectural features of libraries’ buildings, main architectural styles, professional biographies of eminent architects are examined in the course. Practical trainings include developing a library building draft. The libraries’ interior design is carried out in 3D-models and compact layouts on physical media. The educational process is organized in close cooperation with professionals in the field of architecture, particularly with the leading teachers of the Department of the Interior and Equipment of St.-Petersburg State Art-Industrial Academy. They provide methodical assistance and scientific advice, thus the course get the necessary format of teaching and the complexity level of formed competencies, which is available for non-architect students taking into account their existing knowledge, skills and abilities.